Computational Analysis of Biophilic Scale Distributions of Façades in Kaunas City Centre - Ivaskevicius, Marius; Dogan, Huriye Armagan (Landscape Architecture and Art, 2021)
The results of numerous studies which are performed on the concepts of Biophilic architecture demonstrate that it can influence emotional tension and health of the observers. Moreover Biophilic research exhibits that not only natural plants induce biophilic response, but also artificial, human creations with certain fractal dimensions or distributions of scales can have an impact. In that regard, the aim of this research is to describe the relation between measurable Biophilic properties of façades and the emotional tension inducing health problems measured with the count of medical emergency arrivals in the vicinity of the façades. To achieve the aim several tasks were completed, such as the development of a methodology of façade analysis, and application of it in an experiment to test the validity. The engineered features found by this research are based on statistical analysis of distributions of line lengths and distances between lines in a drawing of a façade. To test the methodology, a linear regression model with six features was trained and it achieved a 37 % confidence, measured with R² adjusted, predicting the number of medical emergency arrivals. Simplicity of the model allowed to make additional insights into the specificity of façade properties, and their importance to Biophilia, which establishes the scientific novelty and the significance of this research.